Bentuk Tuturan Persuasif Iklan Layanan Masyarakat di Youtube sebagai Materi Ajar Teks Iklan SMP/MTs - Rini, Arika; Farikah; Mulyani, Mimi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2021)
The writing of this conceptual article is motivated by the existence of teaching materials that have not explicitly conveyed material about pragmatics. There needs to be a written submission and it is stated in the textbook that the material presented is about pragmatic studies. Studies that include persuasive speech seek to influence the reader. Searle's theory of persuasive speech act theory, which includes assertive, commissive, expressive, declarative, and directive speech acts is the subject of study in writing this conceptual article. Armed with these materials, students from the beginning have been prepared as linguists, although it is unlikely that all students are in that direction.